Neutrosophic Logic as an Alternative to Treat Missing Values in Calculating the Stability of Cronbach's Alpha for Psychological and Achievement Tests (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The research aims to use the Neutrosophic Logic, which adopts the logic of non-determinants, in treating the missing values in educational and psychology scales and tests, and to derive the necessary equations for the Cronbach's Alpha consistency equation